Intravitreal Anti-VEGF Injection Monotherapy for Wet Age-Related Macular Degeneration: A Case Report Demonstrating Successful Visual and Anatomical Outcomes - Ramzi Amin; Linda Tri Wulandari (HM Publisher, 2024)
Neovascular (wet) age-related macular degeneration (nAMD) is a leading cause of severe vision loss in the elderly, characterized by choroidal neovascularization (CNV). Intravitreal anti-vascular endothelial growth factor (anti-VEGF) therapy has revolutionized nAMD management. This report details a case of nAMD successfully managed with anti-VEGF monotherapy. A 61-year-old male smoker with a history of hypertension presented with a two-year history of progressive blurred vision in his right eye (OD). Best-corrected visual acuity (BCVA) was 1/300 OD and 6/60 (pinhole 6/30) OS. Fundus examination OD revealed drusen, hard exudates, and reduced foveal reflex. Optical Coherence Tomography (OCT) OD confirmed intraretinal and sub-RPE fluid, pigment epithelial detachment (PED), and features suggestive of Type II CNV. The patient was diagnosed with nAMD OD and immature senile cataract bilaterally. He received intravitreal anti-VEGF injection OD. Seven days post-injection, BCVA OD improved to <1/60, with subjective improvement in vision. In conclusion, this case demonstrates the efficacy of intravitreal anti-VEGF monotherapy in improving visual and anatomical outcomes in a patient with nAMD. Despite known risk factors, timely intervention led to a favorable short-term response. Long-term management and monitoring remain crucial.